Why is Adoption Like a First Nations’ Feast?: Lax Kw’alaam Indigenizing Adoptions in Child Welfare - Bertsch, Maria; Bidgood, Bruce A. (First Peoples Child & Family Review, 2010)
Have you ever wondered about how to be culturally-sensitive in adoption approaches with Aboriginal people? Have you wanted ideas on how to more effectively engage First Nations adoptive-parents? Did you consider how leadership for social workers could assist in adoption outcomes for Aboriginal children? This article chronicles a study of the adoption experiences of the members of a First Nations community in Northwestern British Columbia, Canada. The results indicated that despite an overwhelmingly negative history with the adoptions and child protection system, many First Nations people are not only open to adoption but perceive it as an integral part of their traditional parenting practices. There is an overarching desire to have children who have been previously adopted outside the community returned to their hereditary lands. A series of recommendations for a more culturally-sensitive adoption practice were identified including: 1) improved information, 2) on-going community-government consultation, 3) cultural preservation, 4) social work training, and 5) government policy changes. The article will encourage curiosity regarding social work leadership and how this framework can be instrumental when working with Aboriginal culture. The implications of the study for the role of social workers as leaders in the creation of a new, culturally-sensitive adoption practice are discussed.